2021
DOI: 10.1371/journal.pntd.0009640
|View full text |Cite
|
Sign up to set email alerts
|

Evidence for hidden leprosy in a high leprosy-endemic setting, Eastern Ethiopia: The application of active case-finding and contact screening

Abstract: Leprosy or Hansen’s disease is a disabling infectious disease caused by Mycobacterium leprae. Reliance on the self-presentation of patients to the health services results in many numbers of leprosy cases remaining hidden in the community, which in turn results in a longer delay of presentation and therefore leading to more patients with disabilities. Although studies in Ethiopia show pockets of endemic leprosy, the extent of hidden leprosy in such pockets remains unexplored. This study determined the magnitude… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
10
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 14 publications
(11 citation statements)
references
References 31 publications
0
10
1
Order By: Relevance
“…1 , 15 In this study, the overall AFB positivity rate among Leprosy suspected cases was 10.9%, which was high compared to the report from different regions of the world 16 and a recent report from the Eastern part of Ethiopia. 17 Before initiation of MDT, the prevalence of Leprosy in Ethiopia was 19.8% which was higher than our finding; however, in 2012 it was dropped below 0.5%. 1 The current study showed the increment of Leprosy cases as compared to overall leprosy cases reported in 2012.…”
Section: Discussioncontrasting
confidence: 75%
“…1 , 15 In this study, the overall AFB positivity rate among Leprosy suspected cases was 10.9%, which was high compared to the report from different regions of the world 16 and a recent report from the Eastern part of Ethiopia. 17 Before initiation of MDT, the prevalence of Leprosy in Ethiopia was 19.8% which was higher than our finding; however, in 2012 it was dropped below 0.5%. 1 The current study showed the increment of Leprosy cases as compared to overall leprosy cases reported in 2012.…”
Section: Discussioncontrasting
confidence: 75%
“…In the current study, most registered cases had MB leprosy at the time of diagnosis, which is in line with another study in East Hararghe, Ethiopia reported that 90.9% of cases were MB type leprosy. 31 Other studies in Ethiopia also showed that the percentage of MB cases among newly detected leprosy cases has increased significantly since 2000. 23 Similar findings were also observed in other endemic countries.…”
Section: Discussionmentioning
confidence: 95%
“…Fedis district was randomly selected from the 12 high-leprosy burden districts in East Hararghe. Fedis district has an estimated population of 133,382 and five health centres that provide general health services including tuberculosis (TB) and leprosy control activities [ 26 , 27 ]. Two health centres, namely Boko Health Centre and Fechatu Health Centre, were selected randomly for this study.…”
Section: Methodsmentioning
confidence: 99%
“…Two health centres, namely Boko Health Centre and Fechatu Health Centre, were selected randomly for this study. According to the zonal health office report, 57 leprosy cases were diagnosed in Fedis district in 2017, which indicates a 4.3/10,000 incidence rate (Zonal TB/Leprosy focal person office communication) [ 26 ]. Bisidimo Hospital was selected purposively as it is the only hospital providing dermatology services, including leprosy, in the area.…”
Section: Methodsmentioning
confidence: 99%